2021
DOI: 10.1155/2021/9241338
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis of Financial Statement Fraud of Listed Companies Based on Logistic Regression and Random Forest Algorithm

Abstract: Financial supervision plays an important role in the construction of market economy, but financial data has the characteristics of being nonstationary and nonlinear and low signal-to-noise ratio, so an effective financial detection method is needed. In this paper, two machine learning algorithms, decision tree and random forest, are used to detect the company's financial data. Firstly, based on the financial data of 100 sample listed companies, this paper makes an empirical study on the fraud of financial stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…When Liu conducted research on financial market regulators, they found that there were a lot of financial risks, so they proposed a random forest algorithm to analyze and predict them. The experimental results show that the prediction accuracy of the algorithm is as high as 97%, which shows the accuracy and efficiency of this algorithm [13]. Through previous research, it has been found that the random forest algorithm has been used in various fields and has shown extremely strong performance.…”
Section: Related Workmentioning
confidence: 83%
See 1 more Smart Citation
“…When Liu conducted research on financial market regulators, they found that there were a lot of financial risks, so they proposed a random forest algorithm to analyze and predict them. The experimental results show that the prediction accuracy of the algorithm is as high as 97%, which shows the accuracy and efficiency of this algorithm [13]. Through previous research, it has been found that the random forest algorithm has been used in various fields and has shown extremely strong performance.…”
Section: Related Workmentioning
confidence: 83%
“…The larger the value, the richer the diversity among the classifiers. Kappa statistic is more comprehensive, it can be used to measure the accuracy of the classifier; It can also indicate the consistency of the prediction results of different models, as shown in equation(13).…”
mentioning
confidence: 99%